Toxicity of Eucheuma cottonii seaweed extract with Methanol and N-Hexane solvents for Artemia salina larvae - Kaharudin, Zakaria; Nurrachmi, Irvina; Efriyeldi, Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Seaweeds are very popular in the world of commerce, in science known as algae. Algae consists of four classes: Rhodophyceae (Red Algae), Phaeophyceae (Brown Algae), Chlorophyceae (Green Algae), and Cyanophyceae (Green-blue algae). Seaweed contains secondary metabolite compounds in the form of alkaloids or flavonoids that are useful as medicines and other purposes such as cosmetics and other industries. Seaweed is known to be rich in essential nutrients, such as enzymes, nucleic acids, amino acids, minerals, trace elements and vitamins A, B, C, D, E and K so it is also known as traditional medicine for cough, asthma, bronchitis, tuberculosis, abdominal pain, fever and rheumatism. This research was conducted in February - March 2018 in Sugie Village, Karimun Regency, Riau Islands Province, which aims to produce seaweed extract E. cottonii using Methanol and N-Hexane solvent and knowing LC50 value of Seaweed extract E. cottonii. Data were obtained by using BSLT (Brine Shrimp Lethality Test) method. The results of the study showed that the extract obtained from 5 kg of seaweed (wet weight) as much as 513 mL of concentrated extract. Seaweed extract with type E. cottonii was toxic to test animal A. salina. The LC50 value of E. cottonii extract dissolved in methanol was 40.2438 ppm.Keywords: toxicity, Extract of Seaweed, Desa Sugi